Continuation of the systematic research of a 2nd-century Roman shipwreck off the island of Ilovik (In situ, 2024)
During October 2023, systematic research of the Roman shipwreck remains from the 2nd century AD continued off the island of Ilovik. During the research campaign, fourteen more whole or partially damaged amphorae and four ancient coins were discovered. It was established that the coin found in 2022 was minted in the era of Emperor Hadrian, and four variants of amphorae were recognized among the collected material. A surface survey of the terrain near the pier on Ilovik resulted in the discovery of pottery sherds that could belong to the Neolithic period.
Keywords: shipwreck; antiquityite; Adriatic flat-bottomed amphorae; Roman coins; prehistoric site